The choice of first-line Chronic Myelogenous Leukemia treatment - Fava, Carmen (Ann Hematol, 2015)
Imatinib has represented a revolution in the treatment of chronic myeloid leukemia (CML), inducing an overall survival never seen with previous therapies. However, with the commonly used dosage of 400 mg, one third of the treated patients does not reach the criteria associated with an optimal outcome and could potentially benefit from a different treatment strategy. Several trials exploring modified imatinib-based treatments or second-generation tyrosine-kinase as front-line therapy have been performed. In some studies, high-dose (800 mg per day) or dose-adapted imatinib or imatinib plus interferon was reported to be able to induce better cytogenetic and molecular responses compared with standard-dose imatinib, although no improvements in progression-free survival (PFS) or overall survival (OS) have been so far reported. At the moment, these approaches are still considered investigational. On the other side, on the basis of their capacity to induce very fast and deep molecular responses, including major molecular responses (MMRs) and the newly defined very deep molecular responses MR(4) and MR(4.5), and to prevent at least part of the early progressions to AP/BC that still occur during the first 2–3 years from diagnosis, dasatinib and nilotinib have been approved and registered by FDA and EMA as the first-line therapy for CML patients, opening the possibility to use different therapeutic strategies for newly diagnosed CML patients and a consequent intense debate among hematologists.